Klasifikasi Antara Pelaku Industri Kecil Menengah Aktif Atau Tidak Aktif Dalam Program Pembinaan Legalitas Menggunakan Metode Analisis Diskriminan - Fery Nurmansyah Ardianto; Rusidinyanto (Jurnal Serambi Engineering, 2025)
The problem in this study is that not all SMEs are active in the business legality development programme run by the Mojokerto Regency Trade and Industry Office. There are various factors that can cause this, such as not understanding how to manage business legality and not knowing the benefits of business legality. In this problem, it was analysed using the discriminant analysis method supported by calculations in Excel software. Thus, this study aims to classify SMEs that are active or inactive in the legality development programme. The results obtained based on the discriminant function showed that the first discriminant function had a value of -0.51 and the second function had a value of -0.40. It can be concluded that the classification category of the data is more dominant towards the active SME criteria. The solution that can be implemented is that the Mojokerto Regency Trade and Industry Office is expected to be able to increase socialisation regarding the benefits of the legality development programme so that more SMEs are involved.